Gajah Olen : Preserving a Malay Wedding Traditional through Crowdsourcing Approach - NOR RAS AMIERZA, MARZUKI (Universiti Malaysia Sarawak (UNIMAS), 2020)
Malaysia is multi-racial country that is diverse with culture and heritage due to the existence of different groups of people. In Malay Sarawak marriage, Gajah Olen is one of the traditional costume attires in this state. Unfortunately, the existence of Gajah Olen has sunk in the eyes of the public. This is because the younger generation like to add on some modern touch on the costume and without been notice the traditional costume slowly extinct through the time. There are three main objectives of this project; to design and develop a platform to preserve Malay wedding tradition which is Gajah Olen, to create implicit knowledge of Malay Sarawak wedding tradition by using a crowdsourcing approach and to apply the recommendation system by using collaborative filtering algorithm into a platform for Malay wedding tradition in order to verify the content before publishing it to the public. The data collection techniques used were questionnaires involving respondents which are the general public. To overcome the problem, a platform will be developed to store and preserve the information regarding the Gajah Olen bride attire. In addition, the system was created to facilitate the public who wants to know more about the Gajah Olen. Therefore, with this system, the public will able to access the information to enhance their knowledge about Gajah Olen traditional custom attire so that it will not be forgotten. In order to prove the effectiveness and usefulness of the Gajah Olen Platform, a series of chapters will be further discussed in this report.